Metabolic adaptation to chronic hypoxia in cardiac mitochondria. - Heather, L; Cole, M; Tan, J; Ambrose, L; Pope, S; Abd-Jamil, A; Carter, E; Dodd, M; Yeoh, K; Schofield, C; Clarke, K (2012)
Chronic hypoxia decreases cardiomyocyte respiration, yet the mitochondrial mechanisms remain largely unknown. We investigated the mitochondrial metabolic pathways and enzymes that were decreased following in vivo hypoxia, and questioned whether hypoxic adaptation was protective for the mitochondria. Wistar rats were housed in hypoxia (7 days acclimatisation and 14 days at 11% oxygen), while control rats were housed in normoxia. Chronic exposure to physiological hypoxia increased haematocrit and cardiac vascular endothelial growth factor, in the absence of weight loss and changes in cardiac mass. In both subsarcolemmal (SSM) and interfibrillar (IFM) mitochondria isolated from hypoxic hearts, state 3 respiration rates with fatty acid were decreased by 17-18%, and with pyruvate were decreased by 29-15%, respectively. State 3 respiration rates with electron transport chain (ETC) substrates were decreased only in hypoxic SSM, not in hypoxic IFM. SSM from hypoxic hearts had decreased activities of ETC complexes I, II and IV, which were associated with decreased reactive oxygen species generation and protection against mitochondrial permeability transition pore (MPTP) opening. In contrast, IFM from hypoxic hearts had decreased activity of the Krebs cycle enzyme, aconitase, which did not modify ROS production or MPTP opening. In conclusion, cardiac mitochondrial respiration was decreased following chronic hypoxia, associated with downregulation of different pathways in the two mitochondrial populations, determined by their subcellular location. Hypoxic adaptation was not deleterious for the mitochondria, in fact, SSM acquired increased protection against oxidative damage under the oxygen-limited conditions.